THE IMPLEMENTATION OF GOOGLE CLASSROOM IN TEACHING READING COMPREHENSION NARRATIVE TEXT AT GRADE XI IN MAN 1 MEDAN - Wahyu Ella Anggraini; Masitowarni Siregar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
This research dealt with the Google Classroom used by teachers, how the teachersimplement Google Classroom, and the problems that teachers faced in implementingGoogle classroom in teaching reading comprehension of narrative text at grade eleventh inMAN 1 Medan. This study used descriptive qualitative design. The data were collected byfollowing instruments: observing and interviewing. The findings of this study revealed thatin teaching reading comprehension of narrative text during online there are 5 stages whichare: 1) Access and Motivation, 2) Online Socialization, 3) Information exchange, 4)Knowledge construction and 5) Development.And the problems faced by teachers are:Unstable Network, Quota Limitation and lack of focus caused by appropriate bysurroundings during online teaching learning process.